2003
DOI: 10.1029/2002jc001483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical and radar measurements of surf and swash zone velocity fields

Abstract: [1] Surf zone bore celerities and swash zone surface currents were measured on a shallow sloping, low-energy beach using two remote sensing methods that differ fundamentally in their imaging mechanisms. Microwave Doppler radar measures electromagnetic backscatter from small-scale ocean surface roughness while video-based particle image velocimetry (PIV) relies on image texture resulting from variations in light reflectivity from the ocean surface. Imagery from the two methods showed high correlation, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…This value proved to be independent of the changes in the ambient environmental conditions during the experiment. Being consistent with the findings of previous research [16], [25], [57], it was found that the strongest backscatter comes from the steep and/or breaking waves. However, unlike most results from a deeper water, it is apparent from the present results that, in the surf zone, the depth-limited breaking waves are the more dominant mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…This value proved to be independent of the changes in the ambient environmental conditions during the experiment. Being consistent with the findings of previous research [16], [25], [57], it was found that the strongest backscatter comes from the steep and/or breaking waves. However, unlike most results from a deeper water, it is apparent from the present results that, in the surf zone, the depth-limited breaking waves are the more dominant mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…Although the means of the distributions (Figure 3) associated with the secondary peaks agree well with the predicted phase velocities (Figure 4), pixels with the largest NRCS have higher Doppler velocity values (Figure 3) than predictions. Thus mean Doppler velocities of surf zone bores estimated from the largest individual values of NRCS (Figure 4, squares) (see also Puleo et al [2003, Figure 9c], who use the same data used here) rather than those estimated from the peak of the distribution (i.e., the highest‐valued contours in Figure 3) as used here are significantly larger than predicted velocities (Figure 4). The physical mechanism associated with these largest velocities remains uncertain.…”
Section: Results and Analysismentioning
confidence: 73%
“…Radial velocity versus cross‐shore coordinate (and depth). Asterisks are theoretically predicted shallow water phase velocities (), diamonds are observed radial velocities corresponding to the means of the joint histograms for radar beams from −2.49° to +2.49°, triangles are the observed radial velocities corresponding to the peaks of the histograms, and squares are the observed radial velocities corresponding to pixels with the largest NRCS values [from Puleo et al , 2003]. The RMS difference between the observations (diamonds) and the predictions (asterisks) is 0.17 m/s.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some field observations have suggested that nearshore wave speeds are bounded by this limit (Inman et al, 1971;Thornton and Guza, 1982); although, in a few cases the limit has also been exceeded (Suhayda and Pettigrew, 1977;Lippmann and Holman, 1991;Puleo et al, 2003). In general, there is significant variability between the observed phase speeds and the theoretical predictions.…”
Section: Boussinesq Wave Theorymentioning
confidence: 89%